The INTERCONNECTION OF THE VISUAL IMAGES AND THEMES FOUND IN CHILDREN’S NARRATIVES OF WAR THOUGH DRAWING - Abdussalam, Alaminah (JEE (Journal of English Education), 2024)
The study of children’s drawings has long been an interesting filed in linguistic research. Children’s drawings are an indication of their developmental progress, it is a gateway that offers a window into the children’s internal thinking and attitude. The present study focuses on unveiling the relationship of the images and themes found in the children’s drawings of the Marawi Siege, a war that occurred between the government forces and terrorists in the Southern Philippines in 2017. This study includes 40 drawings of the child-respondents who are residing in the temporary shelters in Boganga and Rorogagus, Lanao del Sur. The interconnection was based on two perspectives, namely: realistic and artistic. In realistic perspective, the drawings were analyzed based on realistic representations of the children of the visual images, in which themes were embedded. In artistic perspective, the attention shifted away from what the children were drawing to the creation process of the visual images and themes. Thus, this study propounds that the children’s psychological process played a significant role in how they drew the scenarios in order to gain an understanding of the reality.